1996
DOI: 10.1007/bf00573857
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell granulomas of the brain: pediatric case presentation and review of the literature

Abstract: Plasma cell granulomas (inflammatory pseudotumors) are benign inflammatory masses that have been observed in virtually every organ system but are most often described in the lung. Rare cases have been reported in which the brain and spinal cord are affected. We present the case of a 5-year-old girl with personality and behavioral changes, discovered to be harboring an intracerebral plasma cell granuloma. The literature on plasma cell granuloma of the central nervous system is discussed with emphasis on the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…10 Like the dural lesions in the present study, IMT has been reported to show commonly low SI on both T2-and T1-weighted images. 5,8,9 Low SI has been explained by the relative lack of free water and mobile protons and/or the presence of free radicals produced by macrophages during active phagocytosis within the lesions of rich fibrosis and collagenous stroma.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…10 Like the dural lesions in the present study, IMT has been reported to show commonly low SI on both T2-and T1-weighted images. 5,8,9 Low SI has been explained by the relative lack of free water and mobile protons and/or the presence of free radicals produced by macrophages during active phagocytosis within the lesions of rich fibrosis and collagenous stroma.…”
Section: Discussionsupporting
confidence: 55%
“…21,25 In addition to similar clinical symptoms and laboratory findings, these similar radiologic features support the argument that both meningeal IMT and idiopathic hypertrophic pachymeningitis are part of a spectrum rather than discrete disorders, even if there were some pathologic differences between the 2 disease entities. 10,21,23,25 As for treatment, surgical resection with adjuvant steroid medication is the treatment of choice for meningeal IMT. 26,27 In our study, there was no recurrence in any patient with localized meningeal IMT following surgical resection with steroid treatment, but all the patients with unresectable diffuse IMT showed various types of recurrence despite the use of multimodal treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It primarily occurs in the lungs [2]. It is also seen to occur in the brain [3], kidney [4], stomach [5] and heart [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the central nervous system is the rare site affected by IMTs, more over 100 sporadic cases have been reported in the literatures [11,26], but intraspinal IMTs were extremely rare. Except our own case, 13 cases of intraspinal IMT have been reported in the literatures.…”
Section: Introductionmentioning
confidence: 99%